Protein Quality Controlling Systems in Plant Responses to Environmental Stresses - Yule Liu (Frontiers Research Topics, 2018)
Environmental stress factors negatively affect plant growth by inducing proteins dysfunction. As coping strategies, plant have developed a comprehensive protein quality controlling system (PQCS) to keep proteins homeostasis. In this research topic of "Protein Quality Controlling Systems in Plant Responses to Environmental Stresses", some latest researches and opinions in this field, including heat shock proteins (HSPs), unfolded protein response (UPR), ubiquitin-proteasome system (UPS) and autophagy, were reported, aiming to provide novel insights for increasing crop production under environmental challenges.